Study of feto-maternal haemorrhage during third trimester of pregnancy and immediate postpartum period in a secondary care hospital in India - Rashmi; Ghoshal, Adrija; Akhtar, Selim; Bera, Tapas Kumar; Dasgupta, Animesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Feto maternal haemorrhage (FMH) & isoimmunisation leads to erythroblastosis fetalis. Post partum Rh anti-D immunoglobulin within 72 hours can significantly reduce the incidence of alloimmunization but about 1.8% women become immunised due to ‘silent’ FMH during third trimester of pregnancy. To find out the incidence & volume of FMH during third trimester of pregnancy and just after delivery. Secondary objective was to consider the justified dose of anti-D immune globulin required after delivery in Rh negative mothers. Methods: After getting approval from institutional ethics committee, we conducted a prospective observational study considering the inclusion and exclusion criteria. We took three maternal blood samples from each mother- at 28, 32 weeks & within 6 hours of delivery for performing Kleihauer Betkes test to detect FMH and its amount. Results: 19 mothers out 0f 100 in our study developed FMH. Out of 19 mothers, 16 (84.2%) mothers had <1 ml Volume of haemorrhage and 3 mothers (15.8%) had 1-3 ml Volume of haemorrhage. We found FMH is statistically associated with maternal blood pressure, mode of placenta delivery & number of foetuses. Conclusion: Though incidence of FMH is low in antepartum period than intrapartum & postpartum period and incidence of large FMH is significantly lower, it is indeed needed to test the volume of FMH in every Rh-negative pregnancy, so that antenatal prophylaxis can be given and no silent bleeds cause isoimmunisation. Routine testing of FMH and subsequent patient specific adjusted dose to prevent isoimmunization can be cost effective.